PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS ARTICULATE STORYLINE TERHADAP HASIL BELAJAR PESERTA DIDIK SMP NEGERI 22 SURABAYA PADA MATERI LISTRIK STATIS - Putriyana Permata Sari Kuraesin; Tatik Indayati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The use of Articulate Storyline in designing interactive learning media can be done easily. The user interface display of Articulate Storyline is similar to Microsoft Powerpoint, it also has a combination of features from media design, interactive question design, as well as a video editor. The purpose of this study was to investigate the effect of using interactive media based on Articulate Storyline on the learning outcomes of class IX students of SMP Negeri 22 Surabaya on the topic of static electricity. The method used is a quantitative descriptive type of quasi experiment with a non-equivalent control group design. The sample consisted of class IX A as the experimental class and class IX B as the control class. Data was collected using test and documentation techniques. The results showed that there was a significant effect of the use of interactive media Articulate Storyline on the learning outcomes of students in the experimental class, with a significance value of 0.000 which is less than the significance level of 0.05. The difference in the average score obtained by the experimental class (86.111) also proved to be higher than that of the control class (74.236). The conclusion is that the use of interactive media is proven to be able to increase students' understanding which is reflected in the increase in their learning outcomes.